Rheological studies of energetic binder-plasticizer blends. (10th November 2021) - Kumari, Dimple; Banerjee, Shaibal
ABSTRACT: Two azido ester plasticizers, bis(1, 3-diazido prop-2-yl) malonate and bis(1, 3-diazido prop-2-yl) glutarate, were mixed with three different binders, Glycidyl azido polymer (GAP), 3, 3-bis-(azidomethyl)oxetane-tetrahydrofuran (BAMO-THF or BT) and 3- nitratomethyl-3-methyl oxetane or Poly NIMMO (PLN) in the ratio of 20:80 (w/w) to study their rheological properties. The addition of plasticizer has reduced the viscosity of three polymer blends, which improved the flow behaviour to an acceptable range. The change in activation energies of polymer blends is also calculated. For all the combination of blends, the rate of change in shear stress and linear range of strain with stress decreases after addition of plasticizers. Variation of viscosity with applied stress is unaffected initially and then increases significantly which limits the linear viscoelastic region (LVR) due to the dilution effect.